Factors affecting electronic procurement usage and their influence to Jordanian firm's performance: the moderating role of top management support - Daoud, Luay Mahfouth (2019)
The government of Jordan has declared as part of its national agenda that Jordan will be among the world-class competitors in knowledge economies by 2018. However, Jordanian firms are underperforming their potential and require more techniques to enhance their performance and increase their competitiveness around the world. In view of this objective, the government has implemented several initiatives to motivate business to use e-procurement. Nonetheless, despite the extensive government efforts, e-procurement usage remains weak among businesses. This study is intended to identify factors that influence e-procurement usage within technologyorganization-environment (TOE) framework and to test how such effects are moderated by top management support. This study sought to determine the influence of e-procurement usage on the firm’s performance. Using a survey questionnaire, 221 responses were received from the Jordanian large firms. Partial Least Squares-Structural Equation Modeling (PLS-SEM) has been applied to analyze the data. The outcomes of this study show that relative advantage, compatibility, organizational readiness, information system committee, competitive pressure, and rules and regulations have significant and positive influence on e-procurement usage. Meanwhile, business complexity has a significant and negative influence on e-procurement usage. Furthermore, the use of e-procurement has a significant and positive influence on firm’s performance. The findings also indicate that the moderating role of top management support has a positive relationship with relative advantages and organization readiness and had a negative relationship with business complexity. The model explained 77.4% of the variance of the eprocurement use and 60.3% of the variance of firm performance. The findings of this study provide valuable information to the government of Jordan which could assist in designing and initiating suitable policies and programs to promote the level of e-procurement usage among Jordanian firms.